(untitled) (Impetus, 2023)
Throughout history, women have been conditioned by stereotypes, gender and inequalities affecting their development at a social and sporting level, since past eras the Victorian ideology presents women as strong morally and spiritually, although physically and intellectually weak. Over time, women have created revolutions to generate social a change that allows them equal rights and freedom in their different roles. This research aims to recognize the feminine in the social and sports field within the Poraû women’s circle of the University of Cundinamarca, focusing on participatory action research and a critical social paradigm through the systematization of experiences which allows to give them value to the knowledge of the people through a process of reconstruction and reflection from the feminine expression, having as a conclusion that the women’s spaces allow to generate free expression, liberation and reflection in the participants, thus improving their interpersonal relationships in their various fields whereby these spaces are of vital importance to reduce such problem.